2019
DOI: 10.1093/mspecies/sez019
|View full text |Cite
|
Sign up to set email alerts
|

Lynx canadensis (Carnivora: Felidae)

Abstract: Lynx canadensis Kerr, 1792, commonly called the Canada lynx, is a medium size felid and is the second largest of the four species in the genus Lynx. It is distributed throughout the boreal forest of most of Canada and Alaska and across portions of the northern United States. It prefers dense, regenerating coniferous forests with moderate canopy and understory cover. L. canadensis is a snowshoe hare specialist, and its ecology, morphology, and behavior closely reflect that of its main prey. It is listed as "Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 185 publications
0
6
0
Order By: Relevance
“…rufus , there is a distinct horizontal ridge superior to the distal articulation on the posterior surface, and a lack of mediolateral constriction between the diaphysis and epiphysis. Lynx rufus is known from the Rancholabrean of Mexico (Ferrusquía-Villafranca et al, 2010) and Arizona (Mead et al, 2005), whereas Lynx canadensis has not been found south of Utah (Lavoie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…rufus , there is a distinct horizontal ridge superior to the distal articulation on the posterior surface, and a lack of mediolateral constriction between the diaphysis and epiphysis. Lynx rufus is known from the Rancholabrean of Mexico (Ferrusquía-Villafranca et al, 2010) and Arizona (Mead et al, 2005), whereas Lynx canadensis has not been found south of Utah (Lavoie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we were able to show that with flexibility in determining monitoring objectives (such as adapting the targeted precision of detectable changes), the majority of other species may be also be covered. As an example, a protocol targeting a 25% decline in marten occupancy would allow the detection of a 50% decline across at least some portions of lynx occupancy (a species of conservation concern in the US 28 ). Increasing the precision to detecting a 10% marten decline, while requiring a more intensive (yet potentially still feasible) protocol, would allow much better monitoring for lynx: 50% decline anywhere surveyed, and extensive areas detecting a 25% lynx occupancy decline.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also supported by the fact that confluent foramina are also found in the bobcat Lynx rufus (Larivi ere and Walton, 1997), which is commonly considered the sister taxon to all the other extant lynxes (Werdelin, 1981;Bininda-Emonds et al, 1999;Johnson et al, 2004Johnson et al, , 2006. On the contrary, the Canadian lynx Lynx canadensis shares with L. lynx the presence of a clear septum separating the two foramina (Lavoie et al, 2019). However, the phylogenetic relationships of L. canadensis are not clear, as it is considered as the sister taxon of L. lynx by some authors (Werdelin, 1981;Bininda-Emonds et al, 1999), or as the sister taxon of the clade formed by L. lynx and L. pardinus by others (Johnson et al, 2004(Johnson et al, , 2006.…”
Section: Taxonomymentioning
confidence: 93%